2015
DOI: 10.4236/jep.2015.65045
|View full text |Cite
|
Sign up to set email alerts
|

The Neighborhood Scale Variability of Airborne Particulates

Abstract: Airborne particulates play a central role in both the earth's radiation balance and as a trigger for a wide range of health impacts. Air quality monitors are placed in networks across many cities globally. Typically these provide at best a few recording locations per city. However, large spatial variability occurs on the neighborhood scale. This study sets out to comprehensively characterize a full size distribution from 0.25 -32 μm of airborne particulates on a fine spatial scale (meters). The data are gather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…It suggests that adjacent locations as far as 10 km also affect the PM2.5 concentration in addition to local factors, indicating the broader scale at which spatial processes driving PM2.5 are operating. Harrison et al (2015) collected street-level PM2.5 data in our study region's 10 km by 10 km area. Their study found that depending on weather conditions, the spatial scale of PM2.5 variation in the area varied between 0.8 and 5.2 km.…”
Section: Discussionmentioning
confidence: 99%
“…It suggests that adjacent locations as far as 10 km also affect the PM2.5 concentration in addition to local factors, indicating the broader scale at which spatial processes driving PM2.5 are operating. Harrison et al (2015) collected street-level PM2.5 data in our study region's 10 km by 10 km area. Their study found that depending on weather conditions, the spatial scale of PM2.5 variation in the area varied between 0.8 and 5.2 km.…”
Section: Discussionmentioning
confidence: 99%
“…However, traditional monitoring of urban air quality faces several shortcomings. First and foremost, the conventional monitoring of urban air is stationary, sparse, and typically remote from human activities, and as such, it poorly resembles air inhaled by people (Miller et al, 2007;McKone et al, 2009;Goldman et al, 2010;Harrison et al, 2015;Pearce et al, 2016). This has been confirmed in studies that deployed wearable monitors and samplers for measuring PM 10 (Jenkins et al, 1996;Scapellato et al, 2009;Broich et al, 2011), PM 2.5 (Andresen et al, 2005;Crist et al, 2008;Steinle et al, 2015), PM 1 (Williams et al, 2000;Johannesson et al, 2007;Velasco and Tan, 2016), CO 2 (Gall et al, 2016), CO (Huang et al, 2012), NO x (Xu et al, 2017) and various volatile organic compounds (Rotko et al, 2000;O'Connell et al, 2014;Manzano et al, 2018).…”
Section: Outdoor Iot Sensing Of Air Qualitymentioning
confidence: 99%
“…In contrast to data from fixed-ground monitoring stations, which are often sparsely located, mobile monitoring platforms provide flexibility to gather data at high spatial resolutions and temporal frequencies. Recently, several studies used mobile monitoring platforms to measure pollutant concentration [2][3][4][5][6]. These studies involved data collection across roads in urban areas using vehicles as a platform for PM2.5 monitoring [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies used mobile monitoring platforms to measure pollutant concentration [2][3][4][5][6]. These studies involved data collection across roads in urban areas using vehicles as a platform for PM2.5 monitoring [2][3][4][5][6]. Some studies used aerial platforms to study the horizontal and vertical profiles of PM2.5 [7,8].…”
Section: Introductionmentioning
confidence: 99%